(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: As ocular trauma is a common type of pediatric trauma, can present with a variety of clinical manifestations, potentially leading to visual impairment and blindness, there is a need for novel methods of reconstructive surgery for severe sequelae of globe injury. Purpose: To analyze the course and outcome of pole-to-pole surgery performed by two teams of surgeons to relieve the sequelae of a severe penetrating globe injury in a child. Material and Methods: The data on the clinical state of the eye after a severe penetrating corneoscleral laceration with contusion component, examination results and pole-to-pole surgery outcomes were reported. Results: Because the state of the affected eye was very poor, the amount of reconstructive surgery was increased. Particularly, in the anterior segment, subluxated capsular bag was secured to the sclera, capsular ring was implanted and open and closed iridoplasties were performed, whereas, in the posterior segment, not only fibrous vitreous and the posterior hyaloid were removed as completely as possible, but also vitreous strands and adhesions that caused retinal tractions were trimmed, epiretinal membranes removed, and circular retinotomy and subsequent endolaser coagulation performed, thereby enabling unfolding the retina. Conclusion: First, in a severe post-traumatic injury to the pediatric eye, a pole-to-pole surgery can be performed with a good outcome. Second, the use of cutting edge technologies with advanced microsurgical tools and support in pediatric patients allows preserving a severely traumatized eye, arresting the inflammatory process, and avoiding subatrophy progression.